PEMULIHAN ASET KORBAN PENIPUAN SEBAGAI TINDAK PIDANA ASAL DALAM TINDAK PIDANA PENCUCIAN UANG - Andreanto; M. Arief Amrullah; Fanny Tanuwijaya (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2023)
: In a criminal offense we need to know clearly the criminal offense that occurred is a must. One of them is the crime of embezzlement formulated in Article 372 of the Criminal Code, which means that embezzlement is an act in which an object is in the power of a person not because of a criminal offense, but because of a legal act, for example because of storage, entrustment agreements, and so on. Then the person who is given the trust to store and so on controls the goods for himself unlawfully, then the person is committing embezzlement. In contrast to fraud as formulated in Article 378 of the Criminal Code, fraud means an act with the intent to unlawfully benefit oneself or others by using a false name, false dignity, deception or lies that can cause others to easily surrender their goods, money or wealth. These two criminal offenses can result in other actions that harm others with economic motives, which can be said that fraud and embezzlement are carried out to obtain a person's assets, one of which can be obtained by money laundering. Assets themselves are goods which in the legal sense are movable objects, both tangible and intangible, which are included in the assets or wealth or property of an agency, business entity organization or individual. The anti-money laundering regime in Indonesia has given birth to a new approach that no longer focuses on the perpetrators of crime, but on the assets of the proceeds of crime, known as the follow the money method. In addition, the law enforcement instruments against illegal assets contained in the Anti-Money Laundering Law are actually sufficient to reach not only the assets resulting from criminal acts but also their acquisition. Ideally, the assets resulting from the criminal offense are returned to the victim of the criminal offense through a court decision with permanent legal force that orders the seizure of assets for the state or returns to the rightful owner. Returning assets to victims by perpetrators in cases of property crime, fraud and embezzlement is not impossible. Return of assets in the form of compensation in this case can be implemented by merging cases. Victims of crimes with material losses, such as fraud and embezzlement, have the right to recover their property.